Hubungan Beban Kerja dengan Stres Kerja Perawat di Unit Rawat Inap RSUD Budhi Asih, Jakarta Timur - Firdiansyah Firdiansyah; Diana Barsasella; Evi Vestabilivy (Jurnal Persada Husada Indonesia, 2017)
Excessive or low workload can cause work stress. Job stress is an individual psychological response to workplace demands that, according to one adapt, to overcome it. Stress work is a response of a person to the demands of the work of RSUD Budhi Asih is a health care agency under the auspices of DKI Jakarta Provincial Health Office. Consisting Of One Of The RSUD Budhi Asih East Jakarta. This research is aimed to find out the relationship between stress burden and work of nurses in the inpatient unit of RSUD Budhi Asih East Jakarta. The type of quantitative research with overwhelming Katan cross sectional conducted on 60 nurses at Inpatient Hospital of Budhi Asih Hospital in east jakarta on June until July 2017. The result showed that the work load was not heavy 21 respondents (35, O%) than the heavy 39 Responses (65.0%). From result of chi-square statistic test obtained value equal to p-value (0.000) p-value which mean value relation Between work load with work stress is smaller than p = <0.05. This proves that there is a significant relationship between the workload of nurses on the incidence of stress work in hospitals Budhi Asih East Jakarta. Keywords: Workload, Work Stress, Nurses